Erectile Function and Dysfunction Following Low Flow Priapism: A comparison of Distal and Proximal Shunts - Tabibi, Ali; Abdi, Hamidreza; Mahmoudnejad, Nastaran (Urology Journal, 2010)
PURPOSE: To compare erectile function following low flow priapism in patients undergoing distal and proximal shunts. MATERIALS AND METHODS: From January 1995 to December 2005, we retrospectively studied 16 patients who presented to our medical center with refractory priapism. Of 16 patients, 5 underwent Winter shunt, while El-Ghorab procedure was performed for 7 patients and the remaining 4 underwent Grayhack shunt. Erectile function was assessed in a minimum follow-up of 2 years (range, 2 to 10 years) using erectile dysfunction (ED) intensity scale [Total score: 5 to 10 (severe ED); 11 to 15 (moderate ED); 16 to 20 (mild ED); and 21 to 25 (no ED)]. RESULTS: The mean patients’ age was 40.62 ± 15.27 years. Mean duration of priapism was 51.12 ± 37.99 hours. Of 4 patients (25%) who underwent proximal shunt (Grayhack procedure), 2 (50%) were impotent, 1 had potency, and the other one achieved some penile erection with administration of oral sildenafil. Of 5 patients (31.25%) who underwent Winter procedure, 1 died because of metastatic bladder cancer and of 4 remainders, 2 (50%) had normal erectile function, but 1 patient suffered from recurrent priapism. Of 7 patients (43.75%) who underwent El-Ghorab procedure, 1 was lost for follow-up and of remaining 6 patients, 2 (33.3%) had normal erectile function and 4 (66.6%) were impotent. No surgical complication was seen. Median lag time from priapism till surgery for patients with and without ED was 48 and 26 hours, respectively (P = .22). CONCLUSION: Grayhack shunt is a safe surgical procedure without any major complications and with lower ED rate. Grayhack shunt might be considered as treatment of choice for refractory low flow priapism.